Relevansi Pengetahuan Dengan Pencegahan Covid-19 di Masyarakat - Fahmi Achta Pratama (Jurnal Ekologi, Masyarakat dan Sains, 2022)
The Covid-19 virus globally still cannot be resolved with the increasing number of new cases. For Indonesia, currently there are also increasing cases and cannot be controlled. As a crucial element in the Covid-19 pandemic, the knowledge of the community about Covid-19, is very necessary to prevent Covid-19. Therefore, this article aims to analyze the relevance of the knowledge possessed by the community with the prevention of Covid-19 in the community. This study applies the literature review method, and in data collection, the researchers review articles. From the results of the research conducted, it is known that the knowledge that the public has about Covid-19 has a relationship with the preventive actions they take. The knowledge gained by the community is influenced by several factors such as sources of information, age level, educational characteristics, and type of work. The conclusion of this study is that knowledge is very relevant to the actions taken by the community because knowledge is the basis for thinking to do something, which in this case is the prevention of Covid-19.